The Impact of Baseline Anxiety on Drug Placebo Separation and Drug/Placebo Response in an Acute Schizophrenia Clinical Trial—A Post-hoc Analysis. Issue 1 (28th January 2023) - Kott, Alan; Brannan, Stephen; Wang, Xingmei; Daniel, David
Abstract: Objectives: We sought to evaluate the impact of baseline anxiety levels on drug placebo separation and drug and placebo response in acutely psychotic schizophrenic subjects. Methods: In this post-hoc analysis, modified intent-to-treat Positive and Negative Syndrome Scale data were obtained from a phase 2, multi-center, 5 week, randomized, double-blind, placebo-controlled trial of KarXT in hospitalized adults with DSM-5 schizophrenia experiencing an acute exacerbation or relapse of symptoms. We investigated the impact of anxiety on drug placebo separation and drug and placebo response in 2 ways. In the first set of analyses, we dichotomized the data based on the absence or presence of anxiety symptoms. In the second set of analyses, we categorized subjects by levels of anxiety. All analyses were conducted using generalized linear models with normal distribution and identity link function. Results: On average, subjects entering the trial were suffering from a moderate level of anxiety. Subjects with no baseline anxiety had a significant increase in placebo response, a decrease in drug response and did not separate drugs from placebo. With increasing levels of baseline anxiety, a larger drug placebo difference was observed. Discussion: Our analyses identified that absence of anxiety at baseline was associated with a loss of signal at end of treatment between drug and placebo driven by a differential effect on placebo and treatment response. The effect observed was not related to the overall baseline symptom severity and was not mediated by improvement in anxiety itself. Interpretation of the results is caveated by the retrospective nature of the analyses.